Review of the brevicollis group of the genus Geodromicus Redtenbacher, 1857 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) - Shavrin, Alexey V. (Zootaxa, 2024)
The brevicollis species group of the genus Geodromicus Redtenbacher, 1857 is reviewed. All three Western Palaearctic species of the group, including G. alborzensis sp. n. (North Iran: Alborz Mts.), G. brevicollis Fauvel, 1875 (Caucasus, north-eastern Turkey, north-western Iran) and G. transversus Motschulsky, 1860 (Caucasus) are (re-) described and illustrated. The following new synonymies are established: Geodromicus Redtenbacher, 1857 = Brachydromicus Bordoni, 1993 syn. n., G. brevicollis = G. jarrigeanus Fagel, 1976 syn. n., = G. jarrigeanus ziganensis Coiffait, 1978 syn. n., = G. armeniacus Iablokoff-Khnzorian, 1989 syn. n., and G. transversus = G. flavipes Motschulsky, 1860 syn. n. The following synonymies previously established by Iablokoff-Khnzorian (1989) are confirmed: G. brevicollis = G. latiusculus Eppelsheim, 1878, = G. constricticollis Eppelsheim, 1890. A lectotype of G. constricticollis is designated. A key to species and distributional maps of all species are provided. Two species represent new country records: G. brevicollis for Azerbaijan and Iran, and G. transversus for Georgia and Armenia.